2016
DOI: 10.1186/s12879-016-1960-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between tuberculosis, diabetes and 25 hydroxyvitamin D in Tanzania: a longitudinal case control study

Abstract: BackgroundVitamin D level is inversely associated with tuberculosis (TB) and diabetes (DM). Vitamin D could be a mediator in the association between TB and DM. We examined the associations between vitamin D, TB and DM.MethodsConsecutive adults with TB and sex- and age-matched volunteers were included in a case-control study in Dar es Salaam, Tanzania. Glycemia and total vitamin D (25(OH)D) were measured at enrolment and after TB treatment in cases. The association between low 25(OH)D (<75 nmol/l) and TB was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The study in China estimated the diabetes prevalence based on a combination of self-reported DM, HbA1c measured in capillary finger-prick blood as well as venous blood fasting glucose and glucose tolerance testing. This suggests that the observed DM prevalence in Lao PDR, may even be higher than reported here as adding glucose to the DM screening tests results in the identification of additional cases [ 14 , 15 ]. The high pre-DM and DM rates with a tendency for earlier onset in Asian populations remain partly unexplained [ 16 ].…”
Section: Discussionmentioning
confidence: 70%
“…The study in China estimated the diabetes prevalence based on a combination of self-reported DM, HbA1c measured in capillary finger-prick blood as well as venous blood fasting glucose and glucose tolerance testing. This suggests that the observed DM prevalence in Lao PDR, may even be higher than reported here as adding glucose to the DM screening tests results in the identification of additional cases [ 14 , 15 ]. The high pre-DM and DM rates with a tendency for earlier onset in Asian populations remain partly unexplained [ 16 ].…”
Section: Discussionmentioning
confidence: 70%
“…A total of 24 studies, 1,21–27,29–33,45–47,52–54,56–60 3295 tuberculosis patients and 18 080 healthy controls were included in the meta-analysis of comparing the blood 25-hydroxyvitamin D concentration of the tuberculosis patients with that of the healthy controls (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 47 studies, seven studies reported the vitamin A status, two studies reported the vitamin C status, 33 studies reported the vitamin D status or the number of people with VDD, and five studies reported the vitamin E status in the tuberculosis group versus the control group. The 47 included studies included 32 case-control studies, 1,15,21,[24][25][26]28,[31][32][33][34][45][46][47][48][49][50][51][52][53] seven cross-sectional studies, 21,22,27,29,30,54,55 and eight cohort or nested case-control studies. 16,35,[56][57][58][59][60][61] The study characteristics are shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Regarding the evidences linking vitamin D deficiency to a higher risk of TB, an study in Tanzania, revealed that vitamin D deficiency is related to an increased risk of TB only in patients with persistent hyperglycemia (OR = 4.0, C.I. 0.86–18.54) (Boillat-Blanco et al, 2016), and another study in China showed that patients with more than 10 years of T2D diagnosis have lower levels of vitamin D (Zhao et al, 2018). In addition to these data, an study in Chinese patients showed that both T2D and pre-T2D people have lower levels of vitamin D in serum (Zhao et al, 2017).…”
Section: Physiopathological Mechanisms Altered In T2d and Their Relatmentioning
confidence: 99%